A serological and molecular survey of Ehrlichia canis in dogs from a community in Aragua State, Venezuela - Martínez A., María del Carmen (2015)
The aims of the study were to determine the prevalence of antibodies anti-E canis and the molecular detection of E. canis as well as to determine the species and level of tick infestations in dogs from a rural community in Aragua state, Venezuela. Blood samples from 110 domestic dogs were obtained and analyzed by Indirect Immunofluorescence (IFI) and Nested Polymerase Chain Reaction (PCR). The seroprevalence was 77.3% and the molecular detection was 45.2%. The percentage of dogs infested with ticks was 69%, mostly with Rhipicephalus sanguineus. The results showed that 80% (68/85) of seropositive dogs and 32% (8/25) of seronegative dogs were tick infested (OR=8.5, 95%, CI 3.19 to 22.6; p<0.00001).